2012
DOI: 10.1080/15374416.2012.711708
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions in Vulnerability to Depression Among Youth: Integrating Risk Factors and Processes Across Multiple Levels of Analysis

Abstract: Depression is a developmental phenomenon. Considerable progress has been made in describing the syndrome, establishing its prevalence and features, providing clues as to its etiology, and developing evidence-based treatment and prevention options. Despite considerable headway in distinct lines of vulnerability research, there is an explanatory gap in the field ability to more comprehensively explain and predict who is likely to become depressed, when, and why. Still, despite clear success in predicting moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 220 publications
(249 reference statements)
4
90
3
1
Order By: Relevance
“…Perhaps most important was that the data were collected longitudinally across an important developmental time span (Hankin, 2012). The use of a longitudinal, cohort sequential design enabled us to measure the prospective association between peer victimization experiences and later depressive symptoms, while controlling for individual differences in baseline depressive trajectories.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps most important was that the data were collected longitudinally across an important developmental time span (Hankin, 2012). The use of a longitudinal, cohort sequential design enabled us to measure the prospective association between peer victimization experiences and later depressive symptoms, while controlling for individual differences in baseline depressive trajectories.…”
Section: Resultsmentioning
confidence: 99%
“…However, individuals do not have equal depressive reactions to victimization (Hankin, 2012). Gottfredson (1989) reported that some, but not all, individuals developed severe or prolonged depressive symptoms following severe victimization, and Foshee et al (2013) detected significant inter-individual variation in depressive symptoms following psychological victimization among adolescents.…”
Section: Heterogeneity In Level Of Depressive Symptoms Following Peermentioning
confidence: 99%
“…These cognitive products and processes have been integrated within other levels of analysis and systems, including genetics (e.g., 67), stress biology (e.g., 46), cognitive/affective neurosciences (e.g., 68, 69), and interpersonal influences. For example, successful cognitive reappraisal protects against the depresogenic GxE effect (5- HTTLPR × stress) (70).…”
Section: Cognitive Factors and Processesmentioning
confidence: 99%
“…Stress may play a role in psychological comorbidity and poor chronic disease outcomes [54][55][56] . Furthermore, psychological comorbidity may lead to changes in health behaviors such as poorer diet or sleep hygiene, lower adherence to treatment and increased smoking.…”
Section: The Impact Of Psychological Comorbidity On Ibdmentioning
confidence: 99%